Somdatta Mandal, trans. & ed., Kobi’ & ‘Rani’: Memoirs & Correspondences of Nirmalkumari Mahalanobis and Rabindranath Tagore - Saurav Dasthakur, (Asiatic: IIUM Journal of English Language and Literature, 2021)
.